Harmine Ameliorates Cognitive Impairment by Inhibiting NLRP3 Inflammasome Activation and Enhancing the BDNF/TrkB Signaling Pathway in STZ-Induced Diabetic Rats - Liu, Peifang; Li, Hui; Wang, Yueqiu; Su, Xiaolin; Li, Yang; Yan, Meiling; Ma, Lan; Che, Hui (Frontiers in Pharmacology, 2020)
Diabetes mellitus (DM) is considered as a risk factor for cognitive dysfunction. Harmine not only is effective in improving DM, but also provides neuroprotective effect for central never system diseases. However, whether harmine has any effect on diabetes-induced cognitive dysfunction and the underlying mechanisms remain still unknown. In this study, the learning and memory ability in rat were detected by Morris water maze. The changes of nucleotide-binding oligomerization domain-containing protein (NOD)-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome and brain-derived neurotrophic factor (BDNF)/TrkB signaling pathway were determined by western blot and histochemical techniques both in streptozotocin (STZ)-induced diabetic rat and in high glucose (HG)-treated SH-SY5Y cells. Herein, we found that harmine administration significantly ameliorated learning and memory impairment in diabetic rats. Further study showed that harmine inhibited NLRP3 inflammasome activation as manifested by reduced NLRP3, ASC, cleaved caspase-1, IL-1β and IL-18 levels in the brain of harmine-treated rat with DM. The similar beneficial effects of harmine were observed in HG-treated neuronal cells. Moreover, we also found that harmine treatment enhanced BDNF and phosphorylated TrkB levels both in vivo and in vitro. These data indicate that harmine mitigates cognitive impairment by inhibiting NLPR3 inflammasome activation and enhancing BDNF/TrkB signaling pathway. Thus, our findings highlight harmine may be as a potential therapeutic drug for diabetes-induced cognitive dysfunction.